The effect of the Talking Diabetes consulting skills intervention on glycaemic control and quality of life in children with type 1 diabetes: cluster randomised controlled trial (DEPICTED study). (26th April 2012) - Robling, Mike; McNamara, Rachel; Bennert, Kristina; Butler, Christopher C; Channon, Sue; Cohen, David; Crowne, Elizabeth; Hambly, Helen; Hawthorne, Kamila; Hood, Kerenza; Longo, Mirella; Lowes, Lesley; et al.
Abstract : Objective To evaluate the effectiveness on glycaemic control of a training programme in consultation skills for paediatric diabetes teams. Design Pragmatic cluster randomised controlled trial. Setting 26 UK secondary and tertiary care paediatric diabetes services. Participants 79 healthcare practitioners (13 teams) trained in the intervention (359 young people with type 1 diabetes aged 4-15 years and their main carers) and 13 teams allocated to the control group (334 children and their main carers). Intervention Talking Diabetes programme, which promotes shared agenda setting and guiding communication style, through flexible menu of consultation strategies to support patient led behaviour change. Main outcome measures The primary outcome was glycated haemoglobin (HbA1c ) level one year after training. Secondary outcomes were clinical measures (hypoglycaemic episodes, body mass index, insulin regimen), general and diabetes specific quality of life, self reported and proxy reported self care and enablement, perceptions of the diabetes team, self reported and carer reported importance of, and confidence in, undertaking diabetes self management measured over one year. Analysis was by intention to treat. An integrated process evaluation included audio recording a sample of 86 routine consultations to assess skills shortly after training (intervention group) and at one year follow-up (intervention and control group). Two key domains of skill assessment were use of the guiding communication style and shared agenda setting. Results 660/693 patients (95.2%) provided blood samples at follow-up. Training diabetes care teams had no effect on HbA1c levels (intervention effect 0.01, 95% confidence interval −0.02 to 0.04, P=0.5), even after adjusting for age and sex of the participants. At follow-up, trained staff (n=29) were more capable than controls (n=29) in guiding (difference in means 1.14, P<0.001) and agenda setting (difference in proportions 0.45, 95% confidence interval 0.22 to 0.62). Although skills waned over time for the trained practitioners, the reduction was not significant for either guiding (difference in means −0.33, P=0.128) or use of agenda setting (difference in proportions −0.20, −0.42 to 0.05). 390 patients (56%) and 441 carers (64%) completed follow-up questionnaires. Some aspects of diabetes specific quality of life improved in controls: reduced problems with treatment barriers (mean difference −4.6, 95% confidence interval −8.5 to −0.6, P=0.03) and with treatment adherence (−3.1, −6.3 to −0.01, P=0.05). Short term ability to cope with diabetes increased in patients in intervention clinics (10.4, 0.5 to 20.4, P=0.04). Carers in the intervention arm reported greater excitement about clinic visits (1.9, 1.05 to 3.43, P=0.03) and improved continuity of care (0.2, 0.1 to 0.3, P=0.01). Conclusions Improving glycaemic control in children attending specialist diabetes clinics may not be possible through brief, team-wide training in consultation skills. Trial registration Current Controlled Trials ISRCTN61568050 .